A micro-CT study of the pulp cavity morphology of maxillary fourth premolar teeth in dogs - Morin, Marie-Christine; D'Astous, Jérôme (Frontiers in Veterinary Science, 2024)
IntroductionThe objectives of the present study were (1) to describe the anatomy of the endodontic system of the dog's maxillary fourth premolar tooth (MxPM4) in relation to the morphology of the crown, (2) to determine if variations of the endodontic system exist, and (3) to look at the implications for endodontic treatment.MethodsTen MxPM4 were harvested en bloc and scanned using micro-computed tomography (micro-CT).ResultsThe morphology of the pulp chamber mostly corresponded with the shape of the crown. Three pulp horns were clearly visible and related to the paracone, the metacone, and the metastyle. Nevertheless, the pulp horns of the metacone and metastyle could be fused, partially fused or distinct. Other pulp projections were also present, but rarely, in the parastyle, the protocone, and the plesioconule. All teeth showed a noticeable angulation of an average of 150 degrees at the coronal third of the mesiopalatal canal.DiscussionThus, the most common transcoronal approach for root canal treatment does not allow a straight access to the apex. There were also minor variations in the locations of the canal orifices. This first micro-CT study of the MxPM4 in dogs showed anatomical features and variations of the pulp cavity that have not been described before.